Avaliação de esquemas iniciais desadaptativos da Terapia do Esquema no Transtorno de Acumulação de Animais - Ferreira, Elisa Arrienti (2021)
Introduction: Animal Hoarding Disorder (AHD) is characterized by the accumulation of many animals and the inability to provide basic care, resulting in deterioration. Few studies propose guidelines or intervention protocols. Objectives: This thesis had three distinct objectives: 1) to develop, apply and evaluate training on AHD for health and law professionals, 2) to understand the phenomenon of animal hoarding, based on theoretical foundations of Schema Therapy (ST) and 3) Disseminate technical information about AHD. In order to respond to objectives, two empirical articles were prepared. The first article aimed to evaluate a training offered to professionals working with animal hoarders. in the areas of Health and Law in the public service. The second article aimed to understand, based on the ST theory, which early maladaptive schemas (EMS) of the first domain were developed by individuals who hoarded animals. Methods: In the first article, the effects of training on AHD for professionals were verified. In addition, it was investigated whether the profile of the professional was related to the level of knowledge about AHD and the effects of training. Thus, 82 individuals participated. A sociodemographic data questionnaire and an instrument for assessing knowledge about animal hoarding disorder (pre- and post-training) were applied. The second article presented the understanding, based on the ST theory, in which early maladaptive schemas (EMS) of the first domain were developed by individuals who hoard animals. Four individuals were interviewed by a psychologist. Participants answered a sociodemographic questionnaire and a semi-structured interview adapted from the ST case conceptualization form that investigated data on childhood, adolescence, and parenting styles. Results: The first study showed that in the interviews content from five of the six Early Maladaptive Schemas (EMS) of the first domain of the ST emerged. In the reports the recurrent presence of maltreatment was observed, especially emotional deprivation during childhood, in addition to the low level of education of parents and paternal alcoholism. The second study indicated the knowledge regarding animal hoarding disorder improved significantly in the evaluation performed after the training, with the best results found in younger individuals and with less time in the work position. For the fulfillment of the third objective, a book chapter ―Interventions in AHD‖ presented initial interventions for individuals with TAA. Conclusion: The first study concludes that the evidence of the effectiveness of training on AHD indicates the importance of developing and offering continuing education activities as tools for the qualification of professionals. In the second article, the conclusive data suggest that an investigation from the perspective of ST can provide a better understanding of this pathology and assist in the construction of intervention protocols, since the ST postulates that situations of abuse and neglect in early life can favor the formation of EMS. The main findings of the thesis were: 1) the presence of five of the six EMS of the first TE domain: ―emotional deprivation‖, ―social isolation‖, ―emotional inhibition‖, ―abuse and pessimism‖ and 2) the proposition that collecting and keeping animals could schemas coping with styles.